ELTV Week-in-Review (African Knowledges and the History Publication since the 1970s, 1986)
Ivory Coast vs Ghana played in Liberia (West African Friendship and Solidarity Trophy); Bochum vs Stuttgart in Bochum.
Keywords: Sports